Pengaruh Keepemimpinan Dan Motivasi Terhadap Kinerja Karyawan CV. Adhi Baskoro Perkasa Pangkalanbun - Putri Indah PR; Hari Susanta Nugraha; Widayanto Widayanto (Universitas Diponegoro, 2016)
Human resources is one factor that has an important role in improving employees performance. Given the important role of human resources, the company must pay attention to the factors that effect employees performance. One of the application is good leadership, so that employees can be persuaded to work according to standart and put aside their personal interests. And with motivation will also encourage to work more spirit.This type of research is explanatory research and its aimed to testing the influence between leadership and motivation towards employees performance. Population in this research was the employees in CV. Adhi Baskoro Perkasa Pangkalan Bun, the sampling technique used was sensus sampling. Sample in this research were 35 respondents. Yhe analysis technique is linier regression analysis using SPSS (Statistical Package For The Social Science) as a tool.The results showed that leadership and motivation have positive influence towards employees performance. Motivation has the most influence (29,8%) and the second is leadership (11,3%).